Parental satisfaction with an advanced audiology-led triage service in paediatric ENT outpatient clinics. (1st February 2022) - Pokorny, Michelle A.; Thorne, Peter R.; Lee, Arier C.; Whitfield, Bernard C. S.; Wilson, Wayne J.
Abstract: Objective: The advanced audiology-led service is designed to triage and manage children who are referred to Ear Nose and Throat (ENT) outpatient services with middle ear or hearing concerns. This service has resulted in shorter waiting times for children to receive ENT treatment, and improved ENT capacity. The aim of this study was to explore parental satisfaction with the advanced audiology-led ENT service and to determine if there were cultural or process factors affecting satisfaction. Design: Prospective cross-sectional study using a modified Visit-Specific Satisfaction Questionnaire (VSQ-9) survey. Study Sample: One hundred and thirteen parents of children consecutively attending a first appointment in the advanced audiology-led service recruited between October 2016 and October 2017. Results: There were a total of 100 valid responses (rate of 88.5%). The survey showed high levels of satisfaction. Satisfaction scores were significantly higher for items related to interactions with the audiologist compared to items related to waiting times. There were no differences in satisfaction across cultural groups. Parents were equally satisfied with the service whether their child was managed independently by the audiologist or required another appointment for medical input. Conclusions: The advanced audiology-led service had high levels of satisfaction from parents attending with their children.